The Grounded Theory Review: An international journal - Judith A. Holton (Grounded Theory Review: An International Journal, 2011)
In this issue, we present one of Barney Glaser's classic papers, The Local-Cosmopolitan Scientist, originally published in 1963. In this paper, we see how he used secondary analysis of survey data to conceptualize and propose a theory of local and cosmopolitan as a dual orientation rather than the perspective of the time which presented them as dichotomous. In his concise explanation of his methodological approach, we see the early emergence of classic grounded theory methodology and its power to use any data.